Effect of New Mesh Fins on the Heat Storage Performance of a Solar Phase Change Heat Accumulator - Zihan Zhao; Jingzhi Jiang; Jingzhou An (Energies)
In view of the problems of slow heat storage process and uneven temperature distribution in the existing phase change heat accumulator, a new type of mesh fin heat accumulator was designed and developed which increased the contact area between the phase change material (PCM) and the fins, enhanced the apparent thermal conductivity of the PCM, improved the heat storage efficiency of the heat accumulator, blocked the PCM, improved the natural convection erosion of the PCM on the upper and lower parts of the heat accumulator, and melted the PCM in each area more evenly. Fluent15.0 was used to numerically simulate the heat storage process of the mesh fins heat accumulator with the finite volume method. The composite PCM prepared by adding 10% mass fraction of expanded graphite to paraffin wax was used as the heat storage material. A 2D, non-steady-state model, incompressible fluid, and the pressure-based solution method were selected. The energy model and the solidification and melting model based on the enthalpy method were used to simulate and calculate the phase change process of PCM. The PISO algorithm was used. The influences of the structural parameters of the mesh fins on the heat storage condition of the heat accumulator were investigated by numerical simulation. The results showed that with the increase in the radius R of the mesh fin, the heat storage time decreased first and then increased. With the increases in vertical fin thickness c, mesh fins thickness δ, and vertical fins number N, the heat storage time decreased. The optimal mesh fin structure parameters were R = 33.5 mm, c = 3 mm, δ = 3 mm, and N = 8, and the heat storage time was 8086 s, which is 47.8% shorter than that of the concentric tube heat accumulator. Otherwise, with the increases in vertical fin thickness c, mesh fins thickness δ, and vertical fins number N, the PCM volume decreased, which shortened PCM melting time.